Cross-age peer tutoring using a design-based research approach to expand computer science education in schools - Schmer, Anne-Maria; Wegner, Claas (American Journal of STEM Education, 2026)
In times of increased demand for the implementation of computer science as a compulsory subject in schools in Germany, additional human resources are required. These are reduced due to the shortage of skilled workers. The concept of "learning to teach" and cross-age peer tutoring enables older students to teach younger students, which has been shown to have positive effects on both groups. This approach is to be realized and evaluated in the "Minteers" project in order to develop a solution approach for lessons in computer science. Based on the design-based research approach, a solution for a concept in cross-age peer tutoring for schools is being explored. This is based on a preliminary examination of the conceptual foundations, followed by testing of the prototypes with the implemented didactic concepts. In the evaluation phase, the concepts and the materials are now being continuously developed and adapted.